2017
DOI: 10.1007/s11604-017-0710-3
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the origins of the thyroid arteries on CT angiography

Abstract: The visualization of thyroid arteries on CT angiography images enables the anatomy of the arterial supply system of the thyroid gland to be explored in a noninvasive manner prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
3
29
3
1
Order By: Relevance
“…In the standard anatomical, surgical and radiological textbooks, the STA is considered to have a relatively constant origin from the anterior surface of ECA[ 19 , 20 ]; but many studies have reported wide variations in the origins of the STA[ 2 , 8 , 21 – 23 ]. The STA frequently arises from the ECA just above the carotid bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…In the standard anatomical, surgical and radiological textbooks, the STA is considered to have a relatively constant origin from the anterior surface of ECA[ 19 , 20 ]; but many studies have reported wide variations in the origins of the STA[ 2 , 8 , 21 – 23 ]. The STA frequently arises from the ECA just above the carotid bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 , 9 Angiologists and head and neck surgeons should be familiar with variations in the origin and course of the principal arteries of the head and neck during surgical procedures and treatment of the upper larynx, parathyroid and thyroid glands. 10 Esen et al 11 advise conducting a thorough CT angiograph study to understand the arterial system of the head and neck region prior to any surgical approach. Thyroidectomy is the most common head and neck surgery done worldwide and the mortality rate is considered to be 0%.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture was maintained for about 4 hours in open air until vapor stoppage before microwave digestion under the following conditions:600 W, 200 °C, 20 min and 150 psi 29,30 .The digested samples were filtered, transferred to polyethylene containers diluted with 0.2 M HCl to appropriate volumes and stored at 4ºC until analysis. The solid residue was discarded.…”
Section: Sample Treatment For Determination Of the Total As Content Imentioning
confidence: 99%